(untitled) (Research, Society and Development, 2022)
The bioactive potential of wood phenolics has been increasingly emphasized. Several authors have researched the phenolic structures transferred to cachaça stored in various native woods. However, there are still no chemical parameters for monitoring/standardizing the stages of maturation/aging of cachaça. Due to the lack of criteria and legal requirements, the beverage labels almost always inform only the popular name of the wood of the barrels/vats. In this work, cachaças from eight Brazilian states (PA, RN, PE, PB, BA, ES, MG and SP) were analyzed. The samples were grouped according to the informed wood and submitted to high performance liquid chromatography to quantify nine previously selected phenolic compounds. The results proved the possibility of identifying woods based on chromatographic similarities and predominant structures. However, there were marked discrepancies between the five samples stored in “balsam”. In Brazil, this name (balsam) is popularly applied to several native species according to the geographic region of origin. Therefore, it is recommended to adopt the scientific name of the wood of the barrels in the beverage labeling, as a starting point for regulation and advances in the certification of origin and safety for consumers.